IMPLEMENTASI TEORI BELAJAR JEAN PIAGET PADA MATAPELAJARAN PAI DI MA UNGGULAN AL-IMDAD BANTUL - Nur Ahmad Fauzi; S Suyadi (Murabby: Jurnal Pendidikan Islam, 2020)
In teaching and learning activities, the teacher in giving understanding to students cannot be limited to being told, it needs development for each student subject. to see how the implementation of constructivism learning theory in madrasas. Then the research used by the writer is field research that uses qualitative data selected as a location to investigate objective symptoms that occur at that location. The location is in MA Featured Al-Imdad. PAI Madrasah Aliyah Featured Al-Imdad's teacher strategy in implementing the theory of constructivism that is the principle teacher teaches children to solve a problem, students present a problem and encourage students to be creative in solving problems faced with thoughts and ideas so that agreement will emerge from the results of what has been achieved captured from student perception